Analisis Semiotika terhadap Representasi Wahyu dan Mukjizat dalam Film Animasi Muhammad: The Last Prophet (2002) Karya Richard Rich - Anabella Nuryafitri; Dadan Firdaus; Alya Fadhillah Harahap; Dafi Al Muyassar Sulaeman (Jurnal Ilmiah Literasi Indonesia, 2026)
This study aims to analyze the representation of revelation and miracles in Richard Rich’s animated film Muhammad: The Last Prophet (2002) using Roland Barthes’ semiotic approach. The study is motivated by the challenge of visually representing sacred events while adhering to the Islamic aniconic principle that prohibits the depiction of Prophet Muhammad. This qualitative research employs a descriptive-analytical approach through the observation of three key scenes: the first revelation in the Cave of Hira, the command of prayer, and the miracle during the Battle of Badr. The data were analyzed using Barthes’ three levels of signification: denotation, connotation, and myth. The findings reveal that the film constructs the representation of revelation and miracles through the use of light, sound, point-of-view shots, characters’ reactions, and environmental changes as a system of signs that establishes an aniconic pattern of “presence through absence.” This strategy enables metaphysical events to be conveyed coherently within the narrative without violating Islamic theological principles. The study concludes that the film successfully bridges transcendental experiences and visual storytelling through a consistent semiotic construction, preserving the sacredness of the events while making them comprehensible to audiences